Synthesis of a novel organosoluble, biocompatible, and antibacterial chitosan derivative for biomedical applications - Rizwan, Muhammad; Yahya, Rosiyah; Hassan, Aziz; Yar, Muhammad; Omar, Ros Anita; Azari, Pedram; Azzahari, Ahmad Danial; Selvanathan, Vidhya; Al-Maleki, Anis Rageh; Venkatraman, Gopinath (Wiley, 2017)
Electrospun materials have a number of applications in the tissue engineering field. However, the limited solubility of chitosan (CS), especially in organic solvents, makes its electrospinning with other synthetic organosoluble polymers impossible. In this article, we report the synthesis of a novel organosoluble derivative of CS through the application of a simple synthetic methodology. CS was reacted with 1,3-diethyl-2-thiobarbituric acid (DETBA) with triethylorthoformate in the presence of methanol and acetic acid (4:1). The functional groups in the synthesized materials were confirmed by Fourier transform infrared and solid-state NMR spectroscopy, whereas X-ray diffraction revealed the level of crystallinity. The CS derivative (CS–DETBA) was tested for its cytotoxic effects on human gastric adenocarcinoma AGS cells and was found to be nontoxic. The prepared derivative showed a much enhanced inhibitory effect on the growth of three bacterial strains, Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus, over that of CS itself. Overall, CS–DETBA showed good solubility in a range of organic solvents, such as dimethyl sulfoxide and N,N-dimethylformamide, and was blended with polycaprolactone (PCL) to form films and electrospun nanofibers. The morphologies of the synthesized materials were analyzed by field emission scanning electron microscopy, and the fiber diameter was 360 nm under optimum conditions. This study demonstrated that the CS–DETBA–PCL blend could be a potential material for tissue engineering and biomedical applications.